GENETIC ALTERATIONS IN MELANOMA - Dunjić, Marija; Perovic, Dijana; Supic, Gordana (Medicinski podmladak, 2024)
Melanoma, an aggressive skin tumor with a high mortality rate in advanced stages, represents a global health challenge. Genetic alterations play a pivotal role in its onset and progression. Recent studies have established a connection between melanoma and changes in signaling pathways involved in cell cycle regulation, notably the MAPK pathway. Over 80% of melanomas exhibit mutations in BRAF, RAS, and NF1, key genes of this signaling chain. Targeted therapies such as BRAF and MEK inhibitors have been developed. However, frequent secondary resistance to this therapy, as well as the existence of melanoma without these mutations, known as "triple wild type", emphasizes the need for further genetic research and improvement of therapeutic strategies. Mutations in genes like KIT, GNAQ/11, PTEN, and TERT are also associated with melanoma pathogenesis, and some of them with specific subtypes of this tumor. Hereditary predisposition is detected in only 5-10% of cases, with CDKN2A and CDK4 identified as the two most common genes in the familial form of melanoma. Exposure to UV radiation has been found as the primary risk factor in shaping the genetic profile of melanoma, leading to the development of "UV signature mutations" that cause further errors in DNA replication and melanomagenesis. Additionally, variations in genes regulating the synthesis of the protective pigment eumelanin during sun exposure, such as MC1R and MITF, pose risks for this disease. Studying precursor lesions, such as melanocytic nevi, has contributed to the understanding of melanoma’s genetic evolution. Identification of mutations like BRAF V600E in these lesions highlights the role of additional genetic changes in malignant transformation. Future research is expected to identify new genetic markers that would improve understanding, prevention, and diagnosis of melanoma, which will enable a personalized approach to treatment with improved efficiency and reduced side effects of therapy.